Effect of calcination temperature on sulfonated lignin catalyst preparation for glucose ethanolysis to ethyl levulinate / Kamarul Ridwan Zainuddin ... [et al.] - Zainuddin, Kamarul Ridwan; Mohamad Zainol, Muzakkir; Hassan, Abdul Hafidz; Asmadi, Mohd; Syed Hassan, Syed Shatir Asghrar; Yusof, Mohd Yazid; Anggoro, Didi Dwi (Research Management Institute (RMI), 2024)
An abundance of biomass material is generated globally which has the potential to be converted to various bio-based chemicals including ethyl levulinate (EL). EL is well known as a sustainable fuel additive and can be produced from glucose, a biomass derivative in an ethanolysis reaction throughout acidic catalysis. In this study, sulfonated lignin carbon catalysts were used to catalyze the ethanolysis of glucose to synthesize EL. The catalysts were prepared from lignin via calcination at different soaking temperatures (400 to 600 °C) for 1 h to produce carbon material, followed by sulfonation with concentrated sulfuric acid at a 1:10 (carbon-to-acid, g/mL) ratio. The catalysts were tested for glucose ethanolysis reaction in a batch reactor equipped with a thermocouple on selected conditions (0.4 g of glucose, 40 mL of ethanol, 1.2 g of catalyst, and 6 h reaction) at 180 °C and their performance was evaluated according to the EL yield obtained. Then, the catalyst characterization was conducted for the selected catalyst using Fourier transform infrared spectroscopy (FTIR), ion-exchange titration, Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX), nitrogen sorption analysis, and Thermalgravimetric analysis (TGA). The result showed that the performance of the sulfonated lignin carbon catalysts was reduced, especially at higher soaking calcination temperatures. The catalyst prepared from lignin carbon calcined at 450 °C, (CS450) was able to provide a high EL yield of 22.54 mol% with a good acidity of 1.0 mmol/g, a high surface area of 229.95 m2/g, and suggested thermal stability at 0300 °C. The results indicated that the sulfonated lignin carbon catalyst could be used as a solid acid catalyst for glucose ethanolysis reaction, yet further catalyst modification is required in the future to enhance its performance for higher EL yield.